Cultivating health and sustainability: the nutritional and environmental advantages of plant-based diets for Tilapia / Izzati Adilah Azmir - Azmir, Izzati Adilah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In recent years, discussions around sustainable and ethical food practices have gained momentum, particularly within the aquaculture industry. One notable advancement involves the shift towards feeding fish with plant-based diets, a trend that not only addresses environmental concerns but also brings forth a myriad of health benefits for consumers. This article delves into the positive impact on human health resulting from the consumption of fish raised on plant-based diets. A trial run of a plant-based diet on Tilapia fish, also known as Oreochromis niloticus, conducted by a team of researchers from UiTM, revealed several potential benefits for humans. One primary advantage is the rich source of omega-3 fatty acids provided by fish fed on plant-based diets, especially those incorporating algae-based supplements. These essential fatty acids play a crucial role in heart health, cognitive function, and reducing inflammation in the body.